Case typologies, chronic illness and primary health care. Issue 4 (29th July 2013) - Griffiths, Frances E.; Lindenmeyer, Antje; Borkan, Jeffrey; Donner Banzhoff, Norbert; Lamb, Sarah; Parchman, Michael; Sturt, Jackie
Abstract Rationale and aims and objectives When assessing patients, clinicians use typologies developed through their own particular clinical experience. Our aim was to develop a typology, based on the patient's perspective and not specific to one illness, with the potential to enhance person‐centred clinical follow‐up of those living with chronic illness. Methods We applied the qualitative comparative method of analysis to interview data from 37 people living with type 2 diabetes or with chronic back pain, recruited from UK General Practices. Informed by theory on time and complexity, analysis focused on the ongoing adjustments made by individuals living with chronic illness (their dynamic) in current time. Health professionals (n = 20) and people living with diabetes or living with back pain (n = 14) refined and validated the typology in five focus groups. Results We identified the following types of dynamic: past reminders, stuck and struggling, becalmed, and submerged. Among interviewees who provided data at different time points, we found some transformed from one dynamic type to another. Conclusion This typology may aid personalization of treatment decisions and could be extended to other chronic illness.